Guest Editor’s Introduction: Creativity and Rationale in Software Design - Carroll, John (Human Technology, 2021)
Creativity and rationale are two lenses for looking at design. Obviously, design is about envisioning new artifacts and experiences through the embodiment of new ideas. But design also is clearly about understanding reasons and balancing trade-offs in order to develop new artifacts and experiences that are desirable and effective, and not merely novel. Because disciplines and predilections tend to fragment and specialize human activity, it can appear that creativity and rationale are about fundamentally different endeavors, although both happen to be known as design. This is profoundly unfortunate; to the extent that such a dichotomy prevails, it more or less ensures that no adequate treatment of design can emerge.